What constitutes patient-centred care for women: a theoretical rapid review - Ramlakhan, Jessica U; Foster, Angel M; Grace, Sherry L; Green, Courtney R; Stewart, Donna E; Gagliardi, Anna R (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Women experience disparities in health care delivery and outcomes. Patient-centred care for women (PCCW) is needed. This study examined how PCC has been conceptualized and operationalized in women’s health research. Methods We conducted a theoretical rapid review of PCCW in MEDLINE, EMBASE, CINAHL and SCOPUS from 2008 to 2018 for studies involving women aged 18 years or greater with any condition, and analyzed data using an established 6-domain framework of patient-centred communication. Results We included 39 studies, which covered the following clinical areas: maternal care, cancer, diabetes, HIV, endometriosis, dementia, distal radius fracture, overactive bladder, and lupus erythematosus. The 34 (87.2%) studies that defined or described PCC varied in the PCC elements they addressed, and none addressed all 6 PCC domains. Common domains were exchanging information (25, 73.5%) and fostering the patient-clinician relationship (22, 64.7%). Fewer studies addressed making decisions (16, 47.1%), enabling patient self-management (15, 44.1%), responding to emotions (12, 35.3%), or managing uncertainty (1, 2.9%). Compared with mixed-gender studies, those comprised largely of women more frequently prioritized exchanging information above other domains. Few studies tested strategies to support PCCW or evaluated the impact of PCCW; those that did demonstrated beneficial impact on patient knowledge, satisfaction, well-being, self-care and clinical outcomes. Conclusions Studies varied in how they conceptualized PCCW, and in many it was defined narrowly. Few studies examined how to implement or measure PCCW; thus, we lack insight on how to operationlize PCCW. Thus, further research is needed to confirm this, and whether PCCW differs across conditions, knowledge needed to inform policies, guidelines and measures aimed at improving health care and associated outcomes for women.